Surveillance of ASF-infected pig farms from September to October 2019 in South Korea - Cho, Ki-hyun (J Vet Sci, 2021)
Fourteen African swine fever (ASF) outbreaks occurred in the pig farms in the northwestern region of South Korea, near the border with North Korea, from September 16, 2019 to October 9, 2019. Active and passive surveillance on the ASF-infected farms indicated that the infection was limited only to pigsties where the infected pigs were detected on the farm for the first time before further transmission to other pigsties and farms. This early detection could be one of the pivotal factors for the prompt eradication of ASF in domestic pig farms within 1 month in the northwestern region of South Korea.